BUCKET PRENEUR: INNOVATIVE BOUQUET AND ACCESSORIES TRAINING TO EMPOWER YOUTH ENTREPRENEURSHIP AND CREATIVITY - Riska Juliarsih (Sean Institute, 2025)
This Student Creativity Program (PKM) aims to enhance the entrepreneurial spirit and practical skills of young people through training in making bouquet crafts and accessories. The program is motivated by the significant potential of the creative industry among youth, especially in handmade products with high market value. The method used was a two-day interactive workshop covering entrepreneurship theory, bouquet crafting practice, and digital marketing strategies. The results showed that 90% of participants successfully created their own products, and 60% expressed interest in starting their own businesses. This activity positively impacted participants by fostering creativity and promoting economic independence. It is expected that this program can serve as a sustainable model for youth empowerment through the creative economy.